Stillbirths In Nepal: A Scoping Review - Dhakal, Keshar Bahadur; Khadka, Damber; Dhakal, Astha; Dhakal-Rai, Sulochana (Nepal Journal of Obstetrics and Gynaecology, 2022)
Stillbirth is the term to describe a foetal demise in utero either prior to, or during the process of labour. It is one of the most burning issues in obstetrics research in recent years. Stillbirth is one of the most heart-wrenching events which can occur unexpectedly during the course of a pregnancy. It causes immense distress to the mother and the health professionals involved. This study aims to explore the incidence, sociodemographic characters, risk factors and obstetrical outcomes related to stillbirths among various studies in Nepal. We searched various electronic databases such as MEDLINE, CINAHL, PubMed, Nepal Journals on-line (NepJOL) and Bangladesh Journals on-line (BanglaJOL) from 2014 to 2021, especially for articles reporting hospital-based stillbirths. We included studies with primary studies on stillbirth conducted in a hospital setting in Nepal and published in English language. The incidence of stillbirths in Nepal varied widely. In this study, the incidence varied from 8 to 23.87 per 1000 births. The majority of stillbirths were preterm, occurring among women aged 20 - 35 years. Many stillborn babies were low birth weight. The categorisation of maternal age and weight of baby, lower limit of gestational week was not similar across the studies. Hypertensive disorders in pregnancy and unexplained factors were the leading risk factors. Limited number of studies available and the lack of uniformity among studies was the main limitation of this review.